Human anatomy : (Gower Medical Pub., 1990)
An atlas of anatomy with substantial accompanying text. Basic anatomical concepts are explained in the opening chapter and, region by region, the subsequent chapters provide a guide to the topography of the entire human body, male and female. The authors attempt in their approach to the subject to bridge the gap between textbook anatomy and a clear understanding of how people are really put together. Photographs of the human cadaver illustrate human structure as it actually appears. The four-colour guides highlight and clarify the structures and relationships shown in each photograph, and place everything within a standard anatomical framework. The text describes the morphology in detail.